The Impact of Modern Markets on Traditional Market Traders' Income - Suyanto, Suyanto (Mahameru Publisher, 2023)
This research examines the influence of modern markets on the current state of traditional markets, which have experienced a declining trend due to the emergence of modern markets that possess the potential to disrupt the traditional market economy. The aim of this study is to analyze the effects of modern markets on the sustainability of traditional markets and their contribution to the economic growth of trade in these traditional marketplaces. The research employs purposive sampling, with a total of 67 respondents, and adopts a quantitative research method. The data analysis model includes simple linear regression, classic assumption tests, and hypothesis testing processed using SPSS. The primary data source consists of responses obtained from questionnaires that gauge the respondents' opinions and assessments of the impact of modern market presence. The results of hypothesis testing indicate a significant positive influence of the existence of modern markets on the sustainability of the traditional Setiabudi SB Group Market. The coefficient of determination reveals that 25% of the variance in the sustainability of the traditional market in Kabupaten Jeneponto is affected by the presence of modern markets.